2021
DOI: 10.31234/osf.io/7waj3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face mask type affects audiovisual speech intelligibility and subjective listening effort in young and older adults

Abstract: Identifying speech requires that listeners make rapid use of fine-grained acoustic cues—a process that is facilitated by being able to see the talker’s face. Face masks present a challenge to this process because they can both alter acoustic information and conceal the talker’s mouth. Here, we investigated the degree to which different types of face masks and noise levels affect speech intelligibility and the subjective effort involved for young (N=180) and older (N=180) adult listeners. We found that in quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
(23 reference statements)
1
14
1
Order By: Relevance
“…Additionally, all listeners were in their early twenties except one (one older listener's score was comparable to the other participants). A preprint study revealed an older group of listeners showed lower audiovisual speech intelligibility scores compared to a group of young adults, and the older listeners subjectively rated that they required more effort to listen to talkers who wore masks compared to young adults (Brown et al, 2021 ). These findings suggest that age may affect speech intelligibility scores.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all listeners were in their early twenties except one (one older listener's score was comparable to the other participants). A preprint study revealed an older group of listeners showed lower audiovisual speech intelligibility scores compared to a group of young adults, and the older listeners subjectively rated that they required more effort to listen to talkers who wore masks compared to young adults (Brown et al, 2021 ). These findings suggest that age may affect speech intelligibility scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study with audiovisual speech found significant effects of a surgical face mask in conditions of low (-3 SNR) and high (-9 SNR) background pink noise on sentence intelligibility (Brown et al, 2021). As our study used longer duration audiobooks, our behavioural measurements might have not been precise enough (i.e only two binary unstandardised 'true or false' statements at the end of each trial regarding semantic comprehension) to detect this influence.…”
Section: Face Masks Increase Subjective Listening Difficulty While Speech Comprehension Is Unaffectedmentioning
confidence: 85%
“…The adverse effect of face masks on speech comprehension has been investigated in various studies on a behavioural level (Brown et al, 2021;Giovanelli et al, 2021;Rahne et al, 2021;Toscano & Toscano, 2021;Yi et al, 2021). Despite the overall agreement of the adverse effects of face masks on speech comprehension, it has been unclear which features of speech processing are specifically affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also have implications for listening situations when relevant visual input from the mouth area is obscured, a topic which has gained enormously in significance due to the wide adoption of face masks to counteract the spread of SARS-CoV-2. In general, listening becomes more difficult and performance declines when the mouth area is obscured (Brown et al, 2021; Giovanelli et al, 2021). While face masks may diminish attentional focusing as well as temporal cues, our work suggests that they also deprive the brain of deriving the acoustic TFS from the lip movements especially in the formant frequency range which are modulated near the lips (F2 and F3).…”
Section: Discussionmentioning
confidence: 99%